Laminin molecules in freeze-treated nerve segments are associated with migrating Schwann cells that display the corresponding alpha6beta1 integrin receptor - Dubový, P; Svízenská, I; Klusáková, I; Zítková, A; Houst'Ava, L; Haninec, P (Glia, 2001)
Isolated acellular nerve segments protected from migration of Schwann cells and the acellular nerve segments joined with the distal nerve stumps were prepared by a repeated freeze-thaw procedure in the rat sciatic nerves. The presence of laminin-1 and -2, as well as alpha6 and beta1 integrin chains, was detected by indirect immunohistochemistry in the sections through acellular nerve segments at 7 and 14 days after cryotreatment. The position of basal laminae and Schwann cells was identified by immunostaining for collagen IV and S-100 protein, respectively. The isolated cryo-treated segment without living Schwann cells (S-100-) did not display immunoreactivity for laminins and integrin chains, while the basal lamina position was verified through the whole segment by immunostaining for collagen IV. The absence of immunostaining for laminin-1 and -2 in cryo-treated nerve segment was verified by Western blot analysis. A crucial diminution of laminin-1 and -2 in the cryo-treated nerve segment of 10-mm length did not abolish the growth and maturation of axons. The greater part of nerve segment connected with the nerve stump displayed no immunohistochemical staining for S-100, corresponding with absence of Schwann cells. The border region of the nerve segment contained Schwann cells (S-100+) migrating from the near-freeze undamaged part of the distal nerve stump. In addition to immunostaining for S-100 protein, the migrating Schwann cells displayed immunostaining for laminins (-1, and -2) and integrin chains (alpha6 and beta1). The results indicate that the presence of laminin molecules in the acellular nerve segments prepared by the repeated freeze-thaw procedure is related with the migrating Schwann cells. The immunostaining for laminins and integrin chains, which constitute one of integrin receptor, suggests an autocrine and/or paracrine utilization of laminin molecules in the promotion of Schwann cell migration.
Keywords: Animals; Female; Brain Tissue Transplantation; Laminin; Integrin alpha6beta1; axony; integrin alfa6beta1; Rats, Wistar; Integrins; transplantace mozkové tkáně; integriny; ženské pohlaví; Schwannovy buňky; laminin; Freezing; Peripheral Nerves; pohyb buněk; periferní nervy; Graft Survival; krysa rodu Rattus; Schwann Cells; Cell Movement; zvířata; zmrazování; přežívání štěpu; Rats; potkani Wistar; Axons